2001
DOI: 10.3346/jkms.2001.16.6.697
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study on the Prevalence of Perennial Allergic Rhinitis and Allergy-Associated Disorders

Abstract: Multicenter Study on the Prevalence of Perennial Allergic Rhinitis and Allergy-Associated Disorders This study was aimed to determine the prevalence of perennial allergic rhinitis (PAR) using the skin test, radioallergosorbent test (RAST), or multiple allergosorbent test (MAST) and to clarify the clinical aspects of the patients diagnosed as having PAR by the questionnaire survey and rhinologic examination. The 71,120 subjects who had visited the 23 otolaryngology clinics at the randomly selected tertiary refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
2
14
2
2
Order By: Relevance
“…Other studies emphasize similar results . This might have resulted from modern living conditions, which enhance susceptibility against allergic diseases …”
Section: Discussionsupporting
confidence: 67%
“…Other studies emphasize similar results . This might have resulted from modern living conditions, which enhance susceptibility against allergic diseases …”
Section: Discussionsupporting
confidence: 67%
“…A previous study in South Korea reported that 40.2% of perennial AR cases had a family history of allergies. Additionally, the incidence of AR in children with a family history of allergies was 1.3-fold higher than in children without a family history of allergies (Min et al, 2001). In the current study, we found that children with a parental history of allergies or a history of allergies within 6 months of birth had a higher frequency of moderate/severe AR as determined by the Spearman test (P < 0.001).…”
Section: Discussionmentioning
confidence: 95%
“…Another study of 1,000 adults with AR found that more than half (56%) of patients experienced rhinorrhea upon awakening [21]. An epidemiologic study of 2,796 outpatients with PAR in Korea found that watery rhinorrhea was the primary symptom in one quarter of patients, second only to nasal obstruction (32%) [22].…”
Section: Impact Of Rhinorrheamentioning
confidence: 98%